2020
DOI: 10.3390/ijerph17176105
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the Mediterranean Diet and Environmental Impact of the Diet on Primary School Children Living in Parma (Italy)

Abstract: The key role of diet in both human health and environmental sustainability is well known. However, there is a lack of studies investigating the environmental impact of children’s dietary behavior. The aim of this observational study was to investigate the dietary environmental impact in a sample of primary school children living in Parma (Italy, n = 172, 8–10 years), in relation to their adherence to the Mediterranean diet (MD). Children completed a 3-day food record in both winter and spring. Dietary records … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 36 publications
(54 reference statements)
0
21
1
1
Order By: Relevance
“…Most of the studies were from countries located in the Mediterranean basin; two studies were conducted in Italy ( 24 , 25 ), two in Lebanon ( 27 , 28 ), two in Spain ( 26 , 29 ), one in France ( 30 ), one in Albania ( 22 ), and one was multicenter (the Netherlands, the United Kingdom, Germany, and Spain) ( 23 ). Five of the nine studies included in this analysis were cross-sectional observational studies ( 22 , 25 , 27 , 28 , 30 ), three were longitudinal observational studies ( 24 , 26 , 29 ), and one was experimental (clinical trial) ( 23 ). Most of the studies were conducted using the dietary consumption data from adults, and one study was conducted using the dietary consumption data from school children ( 24 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the studies were from countries located in the Mediterranean basin; two studies were conducted in Italy ( 24 , 25 ), two in Lebanon ( 27 , 28 ), two in Spain ( 26 , 29 ), one in France ( 30 ), one in Albania ( 22 ), and one was multicenter (the Netherlands, the United Kingdom, Germany, and Spain) ( 23 ). Five of the nine studies included in this analysis were cross-sectional observational studies ( 22 , 25 , 27 , 28 , 30 ), three were longitudinal observational studies ( 24 , 26 , 29 ), and one was experimental (clinical trial) ( 23 ). Most of the studies were conducted using the dietary consumption data from adults, and one study was conducted using the dietary consumption data from school children ( 24 ).…”
Section: Resultsmentioning
confidence: 99%
“…Five of the nine studies included in this analysis were cross-sectional observational studies ( 22 , 25 , 27 , 28 , 30 ), three were longitudinal observational studies ( 24 , 26 , 29 ), and one was experimental (clinical trial) ( 23 ). Most of the studies were conducted using the dietary consumption data from adults, and one study was conducted using the dietary consumption data from school children ( 24 ). Sample sizes vary from 289 to 22,866 subjects for the studies including adults and 172 subjects for the study including school children.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, the results of the present research study are largely similar to those concluded by Asensi et al [ 50 ], who established that following a positive diet was related to the area in which students carried out their day-to-day activities. These outcomes may be explained by the reasons put forth by Galán-López et al [ 51 ] and Rosi et al [ 28 ], who explain that students older than eleven years start to take control over their own diet, in this way increasing their negative dietary patterns. In addition, El Mokhatari et al [ 52 ] concluded that worse dietary outcomes are obtained at the educational stage corresponding to compulsory secondary education, with this stage also coinciding with the start of adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of such foods include legumes, nuts, fruits, and vegetables. It also incorporates vegetable fats, such as olive oil, and prioritises the consumption of fish over red meats [ 26 , 27 , 28 ]. Simultaneously, this diet provides a series of health benefits such as improved blood pressure, attenuated glucose concentration in the blood, reduced likelihood of suffering from diseases that are cardiovascular in nature, and reduced likelihood of suffering from cancer.…”
Section: Introductionmentioning
confidence: 99%